The application of transanal total mesorectal excision for patients with middle and low rectal cancer: A systematic review and meta-analysis. Issue 28 (July 2018) - Hu, Dongping; Jin, Penghui; Hu, Lidong; Liu, Wenhan; Zhang, Weisheng; Guo, Tiankang; Yang, Xiongfei
Abstract: Background: Recently, in order to overcome the shortcomings of laparoscopic surgery in the treatment of low rectal cancer, a new kind of surgical procedure, transanal total mesorectal excision (TaTME), has rapidly become a research hotspot in the field of rectal cancer surgery study. Our study aimed to evaluate the efficacy and safety of transanal total mesorectal excision (TaTME) for the patients with rectal cancer. Methods: Relevant studies were searched from the databases of the Cochrane Library, PubMed, Embase, Web of science. All relevant studies were collected to evaluate the efficacy and safety of TaTME for patients with rectal cancer. The quality of the included studies was assessed by the Newcastle-Ottawa Quality Assessment Scale (NOS) and Cochrane Library Handbook 5.1.0. Data analysis was conducted using the Review Manager 5.3 software. Results: Thirteen studies including 859 patients were included in our analysis. In terms of efficacy, compared with laparoscopic total mesorectal excision (LaTME), meta-analysis showed that the rate of complete tumor resection increased and the risk of positive circumferential margins decreased in the TaTME group. For complete tumor resection and positive circumferential margins in the TaTME group, the odds ratios (ORs) and 95% confidence intervals (CIs) were 1.93 and 1.09 to 3.42 ( P  = .02) and 0.43 and 0.22 to 0.82 ( P  = .01), respectively. Concerning safety, results showed that the rates of postoperative complications were similar in the 2 groups, and differences in the risk of ileus and anastomotic leakage were not statistically significant (OR = 0.75, 95%CI = 0.51–1.09, P  = .13; OR = 0.91, 95%CI = 0.46–1.78, P  = .78; OR = 0.79, 95%CI = 0.45–1.38, P  = .40). Conclusions: The results of this meta-analysis show that TaTME is associated with a reduced positive circumferential resection margin (CRM) rate, and could achieve complete tumor resection and improved the long-term survival in patients with mid- and low-rectal cancer.